Evaluations of patronising communication among Chinese Singaporeans: a study of interactions with older adults in a community-based digital learning context - Toh, Cindy Sing Yee (Nanyang Technological University, 2022)
The population in Singapore is ageing rapidly. Although many issues pertaining to ageing have been addressed over the years, communication with older adults has not been. According to the Communication Predicament of Ageing and Activation of Stereotypes in Interaction models, patronising communication results in negative consequences for its speaker and recipient. This study examines the evaluations of patronising communication among Chinese Singaporeans, the effects of responses by and the gender of older recipients, as well as the impacts of participant characteristics on the evaluations. Video vignettes depicting interactions between a younger and an older adult in a digital learning session in the community were used to elicit reactions from Chinese Singaporean participants. A questionnaire was used to collect data on the participants’ evaluations of the younger speaker’s Accommodativeness and Impoliteness and the older speakers’ Motivation and Negative Affect in the patronising and non-patronising communication conditions. The MANOVA results showed that the Chinese Singaporeans evaluated the patronising speaker as being less accommodating and more impolite, and the corresponding older adult as being less motivated and as experiencing greater negative affect. The evaluations of the patronising style were not affected by the response and gender of the older adult. Across the communication conditions, participants evaluated the older woman more positively, and the younger adult more positively when his interlocutor was the older woman rather than the older man. In addition, findings from the multiple regression analyses indicated that, of the participant characteristics, being female and less educated predicted more positive evaluations of the patronising style. Communication is crucial in the building of a cohesive society. The implications and future directions for communication in ageing studies in Singapore are discussed.